Effects of tropicamide and compound tropicamide eye drops on ocular biological parameters and choroid thickness in children - Mengyue Xu; Na Li; Yan Liu; Yaru Chen; Shuping Xie; Jianfeng Wang (BMC Ophthalmology)
Abstract Objectives To evaluate the effects of short-acting cycloplegic agents, tropicamide and compound tropicamide, on ocular biological parameters and choroid thickness. Methods In this study, seventy pediatric subjects aged 6 to 13 years were randomly assigned to two groups: the tropicamide group and compound tropicamide group. Ocular biological parameters and choroidal thickness (CT) and subfoveal choroid thickness (SFCT) were measured in both groups and were retested 40 min after drug administration. The tropicamide eye drops were administered into the conjunctival sac every 5 min with 1 drop, for a total of 4 doses. Compound tropicamide was administered in the same way as tropicamide. Ocular biological parameters included refraction (spherical equivalent, SE), intraocular pressure (IOP), axial length (AL), anterior chamber depth (ACD), lens thickness (LT), central corneal thickness (CCT), and white to white (WTW). The CT is the regional inferior choroidal thickness of nine sectors centered on the macular fovea and automatically generated using an ETDRS grid. And the SFCT is the choroidal thickness at the subfoveal point of the macular region. Results After application of tropicamide and compound tropicamide to induce the ciliary muscle paralysis, SE, AL, and LT decreased, while ACD, CCT, and WTW increased compared to baseline(all P values < 0.05). There was no significant change in IOP before and after cycloplegia (p > 0.05). The CT in the nasal quadrant before and after ciliary paralysis was significantly thinner than other areas, the CT in the temporal quadrant was significantly thicker than others, and the CT in the inner quadrant was higher than the CT in the outer quadrant. In the tropicamide group: CT was significantly increased in the remaining quadrants except the inner inferior(I) and outer superior(S) quadrants (p < 0.05), and SFCT was also significantly increased (p = 0.005). In the compound tropicamide group: there is a significant increase in CT outer superior(S) quadrant CT (p = 0.043). Increase in the mean values of CT and SFCT in the remaining quadrants was also observed, but the difference was not statistically significant (p > 0.05). Additionally, AL and SFCT were negatively correlated. Conclusions Some ocular biological parameters were altered after application of short-acting cycloplegic agent tropicamide and compound tropicamide to paralyze the ciliary muscle. Compared with compound tropicamide, tropicamide eye drops can reduce axial length while increasing choroid thickness.